The Role of C-Reactive Protein as a Triage Tool for Pulmonary Tuberculosis in Children. Issue 7 (22nd April 2022) - Jaganath, Devan; Reza, Tania F; Wambi, Peter; Nakafeero, Jascent; Kiconco, Emma; Nanyonga, Gertrude; Oumo, Ernest A; Nsereko, Moses C; Sekadde, Moorine P; Nabukenya-Mudiope, Mary G; Kato-Maeda, Midori; Andama, Alfred; et al.
Abstract: Background: C-reactive protein (CRP) has shown promise as a triage tool for pulmonary tuberculosis (TB) in adults living with the human immunodeficiency virus. We performed the first assessment of CRP for TB triage in children. Methods: Symptomatic children less than 15 years old were prospectively enrolled in Kampala, Uganda. We completed a standard TB evaluation and measured CRP using a point-of-care assay. We determined the sensitivity and specificity of CRP to identify pulmonary TB in children using 10 mg/L and 5 mg/L cut-off points and generated a receiver operating characteristic (ROC) curve to determine alternative cut-offs that could approach the target accuracy for a triage test (≥90% sensitivity and ≥70% specificity). Results: We included 332 children (median age 3 years old, interquartile range [IQR]: 1–6). The median CRP level was low at 3.0 mg/L (IQR: 2.5–26.6) but was higher in children with Confirmed TB than in children with Unlikely TB (9.5 mg/L vs. 2.9 mg/L, P -value = .03). At a 10 mg/L cut-off, CRP sensitivity was 50.0% (95% confidence interval [CI], 37.0–63.0) among Confirmed TB cases and specificity was 63.3% (95% CI, 54.7–71.3) among children with Unlikely TB. Sensitivity increased to 56.5% (95% CI, 43.3–69.0) at the 5 mg/L cut-off, but specificity decreased to 54.0% (95% CI, 45.3–62.4). The area under the ROC curve was 0.59 (95% CI, 0.51–0.67), and the highest sensitivity achieved was 66.1% at a specificity of 46.8%. Conclusions: CRP levels were low in children with pulmonary TB, and CRP was unable to achieve the accuracy targets for a TB triage test. Abstract : In a prospective cohort of children with respiratory symptoms in Kampala, Uganda, C-reactive protein levels were low regardless of tuberculosis status and did not achieve the target accuracy for a triage test for pulmonary tuberculosis.